Lexical stylistic devices (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This comprehensive article delves into the multifaceted world of lexical stylistic devices, elucidating their significance in elevating communication across various mediums. Through articulate descriptions and illustrative examples, the piece elucidates a myriad of linguistic tools such as simile, metaphor, wordplay, irony, and repetition, among others. The article underscores how these devices transcend the confines of conventional language, transforming simple phrases into evocative narratives and speeches that resonate with audiences.